2016
DOI: 10.1002/celc.201600183
|View full text |Cite
|
Sign up to set email alerts
|

NiCo2S4 Nanosheets Grown on 3D Networks of Nitrogen‐Doped Graphene/Carbon Nanotubes: Advanced Anode Materials for Lithium‐Ion Batteries

Abstract: To meet the requirements of high‐performance lithium‐ion batteries (LIBs), a new class of electrode materials with favorable nanostructures is highly desirable. Recently, metal sulfides have been intensively studied as promising anode materials for LIBs because of their high lithium storage capacity. Among them, ternary metal sulfides can provide much higher electrochemical activity and energy storage performance than binary metal sulfides or their oxide counterparts, which makes them outstanding candidates as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The NiCo 2 N@C-NCNT nanocomposite electrode showed a capacity fading rate of only 0.089% per cycle at a high current density, which is even smaller than those of previously reported nanostructured NiCo 2 O 4 , NiCo 2 S 4 electrode materials or other electrode materials. 8,[35][36][37][38][39] For comparison, NiCo 2 O 4 -CNT nanocomposite as anodes were also evaluated at a high current density of 2000 mA g À1 , as shown in Fig. 4e.…”
Section: Resultsmentioning
confidence: 99%
“…The NiCo 2 N@C-NCNT nanocomposite electrode showed a capacity fading rate of only 0.089% per cycle at a high current density, which is even smaller than those of previously reported nanostructured NiCo 2 O 4 , NiCo 2 S 4 electrode materials or other electrode materials. 8,[35][36][37][38][39] For comparison, NiCo 2 O 4 -CNT nanocomposite as anodes were also evaluated at a high current density of 2000 mA g À1 , as shown in Fig. 4e.…”
Section: Resultsmentioning
confidence: 99%
“…[33,61,[107][108][109][110] The carbonaceous materials can effectively prevent the agglomeration of nanoscale MMSs, promote electron transport, increase the electroactive sites, and enhance the stability of MMSs.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[109,124,216] The carbon materials can also increase the conductivity of the nanocomposite, resulting in high rate performance and prevent the self-aggregation of NiCo 2 S 4 nanomaterials for better utilization. Zhang et al synthesized a 3D hierarchical nanocomposite composed of ultrathin NiCo 2 S 4 nanosheets and N-doped graphene/CNT (NGC).…”
Section: Ni-co-smentioning
confidence: 99%
See 1 more Smart Citation
“…At about the same time, Jin et al [13] fabricated hierarchical NiCo2S4 hollow spheres, of which possessed a specific capacity of 696 mA•h•g −1 for 100 cycles (0.2 A•g -1 ). Liu et al [26] prepared hierarchical nanostructured hybrids composed by NiCo2S4 nanosheets and nitrogen-doped graphene/carbon nanotube networks, and the composite material displayed high initial charge capacity of 1225.4 mA•h•g −1 (0.2 A•g -1 ). Recently, Xu et al [27] reported NiCo2S4/Ni0.96S nanoparticles anchored in 3D grapheme aerogel, and the material has a superlong cycling stability of 620 mAh•g -1 for 800 cycles (1 A•g -1 ).…”
Section: Li-ion Batteriesmentioning
confidence: 99%